Electrochemical performance of a new structured low temperature SOFC with BZY electrolyte. (12th July 2018) - Chen, Gang; Luo, Yadan; Sun, Wenkang; Liu, Hailiang; Ding, Yushi; Li, Ying; Geng, Shujiang; Yu, Kai; Liu, Guoqiang
Abstract: A symmetrical solid oxide fuel cell (SOFC) with a novel microstructure of BaZr0.9 Y0.1 O3–δ (BZY) as the electrolyte is investigated in this study. The cell with the Ni0.8 Co0.15 Al0.05 LiO2 (NCAL)-foam Ni/BZY/foam Ni-NCAL structure is prepared by a co-pressing method. The maximum obtained power density is 735.6 mW cm −2 in H2 at 550 °C, which is comparable to the results obtained using Ni cermet anode-supported SOFCs with an extremely thin electrolyte. The ionic conductivity of the BZY electrolyte prepared in this study is much higher than that of the conventional BZY electrolyte. The activation energy of ionic conduction is much lower than that of traditional oxygen ion or proton conduction. Electrochemical impedance spectra (EIS) results of the cell with the BZY electrolyte measured in different atmospheric conditions and the results of oxygen ion filtration experiments for the cell using the BZY/Ce0.9 Gd0.1 O2 (GDC) bilayer electrolyte indicate that oxygen ion is one of the carriers in the BZY electrolyte prepared in this study. According to the results of X-ray photoelectron spectroscopy (XPS) and Fourier Transform infrared spectroscopy (FTIR), an interfacial O 2− conduction mechanism at the interface of BZY particles in the electrolyte is discussed. Highlights: A new structured SOFC with BaZr0.9 Y0.1 O3–δ electrolyte was investigated. The peak power density of the cell is 735.6 mW cm −2 in H2 at 550 °C. The BZY electrolyte exhibits very high low temperature ionic conductivity. An interfacial O 2− conduction mechanism of BZY electrolyte was discussed.